Determination of the gamma prime/gamma interface width in a Co–Al–W alloy via coupled aberration-corrected scanning transmission electron microscopy and atom probe tomography. (August 2016) - Meher, S.; Viswanathan, G.B.; Nag, S.; Fraser, H.L.; Banerjee, R.
Abstract: The compositional and order-disorder transition widths of γ′/γ interfaces in a Co–Al–W alloy have been established for the first time by coupling of aberration corrected high resolution scanning transmission electron microscopy and orientation-specific atom probe tomography. While the compositional width is approximately 2.5 nm, the order-disorder transition width is very sharp measuring 0.5 nm. A comparative study revealed that the γ′/γ interfaces, in a model Ni–Al–Cr alloy, are both compositionally and structurally diffuse with nearly the same width (~ 2.5–3 nm). These differences between the γ′/γ interfaces in Co and Ni-base alloys can impact the coarsening behavior of the ordered precipitates. Graphical abstract: